(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Grasscutter serves as a major tool for improved household income generation, nutrition and bio-diversity in Nigeria. It provides a quick turnover, foreign exchange earner and reduce unemployment rate of the country.In order to assess the feeding values of concentrates used as supplement, studies were conducted in captivity to evaluate the performance of Grasscutter (Thryonomys swinderianus) using 20 growing Grasscutters comprising 16 females and 4 males who were balanced for weight and grouped into four treatments. Inclusion of whole cassava meal that was incorporated at 80% of the total bulk acted as the control(T0) while 10% of whole cassava root meal was replaced by fermented soybean meal in (T1), fermented locust bean meal in (T2) and fermented melon seed meal in (T3) respectively were considered as experimental using a complete randomized design. Elephant grass (Pennisetum purpureum) was used as the basal diet and water were given ad libitum. There were significant difference in the final body weight gains (P<0.05) between treatments. The mean final body weights were 1175.0 ±302.01, 1266.7±302.01, 1215±302.01 and 1143.0±302.01g for animals on T0, T1, T2 and T3 respectively. The corresponding mean for final body weight gains were found to be 481±209.55, 536.7±209.55, 507±209.55 and 407±209.55g for T0, T1, T2 and T3 respectively. There were significant differences (P<0.05) in the trunk length in T1 over T2, T0 and T3 and were recorded at the level of4.78±0.19, 4.56 ±0.18, 4.55 ± 0.18 and 4.12 ± 0.16 respectively. The nutrient digestibility of CP, EE, NFE, ADF and ADL were significantly different (P<0.05). The whole cassava root that was combined with fermented soybean meal supported a highest growth rate than those of other treatments. It was therefore concluded that fermented soybean meal may be used as an ideal diet for sustainable Grasscutter production when whole cassava root is combined with this ingredient. J. Bangladesh Agril. Univ. 16(2): 254-259, August 2018